Karakteristik jelly drink rumput laut (Euchema spinosum) dengan penambahan kulit buah manggis (Garcinia mangostana L.) sebagai pangan fungsional - Rahma Utami Budiandari; Syaiful Anam; Lukman Hudi (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Mangosteen fruit (Garcinia mangostana L.) , one of Indonesian fruits, contains 70-75% skin fruit. The mangosteen skin contains xanthone compounds which are antioxidants, 107.76 mg/100 g fresh fruit. Fresh Mangosteen skin is easily damaged, it needs to be processed in order to have a long shelf life, by processing it into a jelly drink. Mangosteen skin extract is formulated with porridge of Eucheuma spinosum to make a jelly drink.This study aimed to determine the effect of the proportion of mangosteen skin extract and seaweed porridge through the physical characteristics, chemical of mangosteen skin extract jelly drink. The method was to design a factorial random group. The first factor is the proportion of mangosteen skin extract and the second factor was the concentration of pure seaweed. Data analyzed with ANOVA and continues with further test BNJ5%. Best jelly drink has an average viscosity 12.67, dietary fiber 2.17%, pH 7.98.